Author Correction: Air-stable superparamagnetic metal nanoparticles entrapped in graphene oxide matrix - Tuček, Jiří; Sofer, Zdeněk; Bouša, Daniel; Pumera, Martin; Holá, Kateřina; Malá, Aneta; Poláková, Kateřina; Havrdová, Markéta; Čépe, Klára; Tomanec, Ondřej; Zbořil, Radek (Nature communications, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.